Calibration and Beam-Mapping Techniques for the Tianlai Pathfinder Dish Array - Oxholm, Trevor (Proceedings of the Wisconsin Space Conference, 2020)
Hydrogen intensity mapping is a promising technique to measuring large-scale structure. By detecting the integrated emission of the 21cm HI signal from many galaxies simultaneously, astronomers can survey larger volumes of the universe than ever before. However, systematics related to foreground subtraction, variable antenna beam patterns, and calibration must be overcome before maps can be made of the 21cm signal. The Tianlai Pathfinder array, a first-generation hydrogen intensity mapping experiment, is being constructed in order to practice and demonstrate our ability to overcome these challenges. We demonstrate two methods, delay-delay rate filtering and point source calibration, in order to understand the systematics of the Tianlai instrument. The methods used here will be used to help demonstrate the feasibility of full-scale hydrogen intensity mapping experiments, while contributing to the experimental toolset used for such experiments.